Children's exposure to alcohol marketing within supermarkets: An objective analysis using GPS technology and wearable cameras. (July 2017) - Chambers, T.; Pearson, A.L.; Stanley, J.; Smith, M.; Barr, M.; Ni Mhurchu, C.; Signal, L.
Abstract: Background and aim: Exposure to alcohol marketing within alcohol retailers has been associated with higher rates of childhood drinking, brand recognition, and marketing recall. This study aimed to objectively measure children's everyday exposure to alcohol marketing within supermarkets. Method: Children aged 11–13 (n = 167) each wore a wearable camera and GPS device for four consecutive days. Micro-spatial analyses were used to examine exposures within supermarkets. Results: In alcohol retailing supermarkets (n = 30), children encountered alcohol marketing on 85% of their visits (n = 78). Alcohol marketing was frequently near everyday goods (bread and milk) or entrance/exit. Conclusion: Alcohol sales in supermarkets should be banned in order to protect children from alcohol marketing. Highlights: Micro-spatial analyses were conducted using paired wearable camera and GPS data. Children are exposed to alcohol marketing on 85% of their visits to supermarkets. Existing legislation does not protect children from exposure to alcohol marketing. Micro-spatial analyses provide insight into health exposures in smaller spatial units.